SISTEM PENYELENGGARAAN DIKLAT JARAK JAUH DI BALAI DIKLAT KEAGAMAAN DENPASAR: DISTANCE EDUCATION AND TRAINING SYSTEM AT BALAI DIKLAT KEAGAMAAN DENPASAR - Hayadin Hayadin (Penamas, 2014)
This research aims at understanding Distance Education and Training System managed by Balai Diklat Keagamaan (the Religious Education and Training Office) in Denpasar, Bali. Aspects of the system under study include inputs, processes, and outputs. This research used a case study method and was conducted from February to September 2011. Interviews, observation, and inventory were used as methods for data collection. Information was obtained from the Head of Balai Diklat Keagamaan Denpasar, Head of Administration Sub-Section, widyaiswara instructors, alumnae of distance education and training programs, and staff of Balai Diklat Keagamaan. The research found that the office has administered distance education and training programs since 2009. Lectures were provided by widyaiswara instructors and supported by administration staff. To improve their knowledge and skills in using distance learning technologies, widyaiswara instructors and support staff had previously been trained in Virtual Learning Environment (VLE) at the Center of Education and Training in Jakarta. Participants of distance education and training came from the provinces of Bali and West Nusatenggara. Learning modules are provided on the website through which learning interactions are also conducted. In addition, there areface-to-face learning sessions. Until 2010, the office already implemented distance education and training programs for 7 batches with the total alumnae of 168 persons. Key Words: Distance education and training, Balai Diklat Keagamaan Denpasar, input, proses, output. Penelitian ini bertujuan untuk mengetahui sistem penyelenggaraan diklat jarak jauh Balai Diklat Keagamaan Denpasar, yakni: input, proses, dan output-nya. Penelitian ini merupakan studi kasus terhadap sistem penyelenggaraan diklat jarak jauh di Balai Diklat Denpasar, Provinsi Bali. Penelitian dilakukan pada bulan Februari hingga September 2011. Teknik pengumpulan data menggunakan metode wawancara, observasi, dan inventori; dengan sumber data terdiri atas: Kepala Balai Diklat Denpasar, Kepala Sub-Bagian Tata Usaha, widyaiswara, alumni peserta diklat jarak jauh dan staf Balai Diklat. Hasil penelitian menunjukkan bahwa Balai Diklat Denpasar telah melaksanakan diklat jarak jauh sejak tahun 2009, memiliki sumber daya pendukung sebagai input penyelenggaraan diklat jarak jauh, yakni: widyaiswara dan staf Balai Diklat yang menjadi tutor dan admin diklat jarak jauh setelah terlebih dahulu mendapatkan pelatihan di Pusdiklat Jakarta untuk mendapatkan pengetahuan dan keterampilan menggunakan Virtual Learning Environtment (internet) melalui internet; tools yang digunakan adalah internet dan modem. Peserta diklat berasal dari wilayah Provinsi Bali dan Nusa Tenggara Barat. Proses pembelajaran dilakukan melalui website diklat jarak jauh sebagai media pembelajaran yang utama. Modul dan materi pelajaran serta interaksi pembelajaran juga dilakukan melalui website. Selain itu, juga ada pembelajaran tutorial yang bersifat tatap muka. Sampai saat ini (2010), Balai Diklat Denpasar telah menyelenggaraan (output) diklat jarak jauh selama 7 angkatan dengan jumlah alumni sebanyak 168 orang. Kata Kunci: Diklat Jarak Jauh, Balai Diklat Keagamaan, input, proses, output